2017
DOI: 10.1080/08039488.2017.1397192
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neutrophil-lymphocyte, platelet–lymphocyte ratio and cognitive functions in bipolar disorder

Abstract: This study revealed negative correlation between NLR and Stroop interference scores. We need further prospective studies with larger sample size to investigate role of inflammation on cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Some studies have suggested that PDW is a more specific marker of platelet activation and is associated with inflammatory vascular damage [28]. Sağlam Aykut et al, who studied cognitive function and NLR, an inflammation marker like PDW, found a negative correlation between inflammatory processes and cognitive functions in BD patients [29]. These studies may suggest that PDW is a predictor of cognitive decline in BD and UD patients due to neuroinflammation.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have suggested that PDW is a more specific marker of platelet activation and is associated with inflammatory vascular damage [28]. Sağlam Aykut et al, who studied cognitive function and NLR, an inflammation marker like PDW, found a negative correlation between inflammatory processes and cognitive functions in BD patients [29]. These studies may suggest that PDW is a predictor of cognitive decline in BD and UD patients due to neuroinflammation.…”
Section: Discussionmentioning
confidence: 96%
“…A Korean study ( 15 ) also found that NLR in the acute phase of stroke was independently associated with an increased risk of PSCI at 3 months and that the highest quintile (NLR ≥ 3.80) increased the risk of PSCI by 3.26-fold compared with that of the lowest quintile ( ≤ 1.57). Other studies, meanwhile, have demonstrated that an elevated NLR is independently associated with an increased risk of AD in people aged > 65 years ( 16 ), with a correlation between NLR and CI ( 13 , 17 , 18 ). A Chinese study of the mild cognitive impairment (MCI) population ( 19 ) revealed that NLR was significantly higher in the MCI group than in that with normal cognitive function, with subjects having an NLR ≥ 2.07 with a nearly six-fold increased risk relative to those with an NLR < 2.07.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these immunological indicators can also be used as a reference for the clinical treatment and outcomes of bipolar disorders. Thirdly, studies have shown that some non-specific immunological indicators (such as central granulocyte/lymphocyte ratio) can predict the suicide risk and cognitive level of patients with bipolar disorder (48,49), which has practical significance for community health management and social function rehabilitation of patients. Finally, through investigation of the pathogenesis of autoimmune diseases, researchers have further speculated about the pathogenesis of bipolar disorder and proposed various mechanisms including cytokine-induced change of monoamine, increased oxidative stress, pathological excessive activation of microglia, excessive activation of the hypothalamus-pituitary-adrenal (HPA) axis, and immune disorder associated with sleep (45).…”
Section: Discussionmentioning
confidence: 99%